Variable methylation of the ribosomal RNA genes of the rat. - Kunnath, L (1982)
Both the pattern and level of rRNA gene methylation vary in the rat. This variation reflects stages in the maturation process and perhaps the level of gene expression in different tissues. We studied methylation at a common site, the inner cytosine of the sequence CCGG, by hybridizing 32P-rRNA to DNA digests obtained with endonuclease Msp I (which cleaves CCGG and CMCGG) and its isochizomer, HpaII (which cleaves only CCGG). In the liver, the changing pattern of rRNA gene methylation reflected the late stages of development: the rRNA genes were mostly unmethylated at 14 days gestation; by 18 days gestation, about 30% of them were methylated, and this level persisted into adulthood. In 18-day DNA, the methylation was uniform, but in adult DNA, the methylation pattern was discontinuous, because otherwise methylated genes contained a demethylated region. Similar developmental changes were observed in brain DNA. In a tissue culture cell line, the change from the continuous to the discontinuous pattern of the methylation could be induced by transformation with Kirsten sarcoma virus. And, in adult tissues, the lowest level of rRNA gene methylation was found in rapidly growing jejunal epithelium, and the highest level, in non-growing spermatozoa.